Attitudes Toward Bisexuality According to Sexual Orientation and Gender. Issue 3 (2nd July 2016) - Hertlein, Katherine M.; Hartwell, Erica E.; Munns, Mashara E.
ABSTRACT: Despite increasing support for lesbian and gay individuals, the same degree of tolerance has not extended to bisexual individuals, and bisexual invisibility and biphobia are continuing problems that affect the mental health and well-being of people who are bisexual. There is evidence that attitudes toward people who are bisexual may vary by one's own sexual orientation or gender. In the present study, the authors examined differences in attitudes toward people who are bisexual by sexual orientation and gender. The authors also asked participants who were bisexual to describe their experiences of being stigmatized. This study found significant effects for sexual orientation but not for gender; specifically, heterosexual participants reported significantly more biphobia and negative bisexual attitudes than participants who were gay, lesbian, or bisexual. Further, participants who were bisexuals reported feeling most stigmatized by individuals who were heterosexual. The results of this study indicate that attitudes toward bisexuality differ by sexual orientation but not by gender. The authors suggest implications for the mental health and well-being of people who are bisexual as well as possible interventions.